Experimental infection of Meriones unguiculatus with subperiodic Brugia malayi: some parasitological observations - Mak, J. W.; Sivanandam, S.; Ngah, Z.; Choong, M. F. (Malaysian Journal of Science, 2017)
The Meriones unguiculatus-Brugia spp. model is used extensively for expenmental studies and for the primary screening of potential filaricides. The parasitological aspects of this model were studied to detennine the optimal conditions for maintaining parasites, screening ofdrugs, and for studies on host-parasite relationships. At autopsy 200 days post-infection, the mean±SD worms recovered from female and male jirds infected with 50 L3 were not statistically significantly different, these being 5.1±6.9 and 8.1±9.2, representing 10.2% and 16.2% ofthe infective dose, respectively. In those given 100 L3, worm recovery from females and males was also not significantly different, these being 20.8±33.5 and 8.5±5.7 respectively. Recovery ofworms was much higher when animals were infected by the intraperitoneal (P) compared to the subcutaneous (SC) route. In those infected with 50 LB, the worm recovery was 15% and 8% by the IP and SC routes respectively. The corresponding figures for animals given 100 L3 were 21 % and 3% respectively. Of the 286 worms recovered, 46% and 54% were females and males, respectively. In infected animals, 80% of the worms were recovered from the peritoneal cavity. In those infected SC, 30% and 33% were recovered from the heart and lungs respectively. The prépatent periods inthose given 501.43 were 172.9±42.3 and 126.3±32.1 days in female and male jirds, respectively, and in those given 50 LB SC were 152.6±44.4 and 150.8±45.3 days, respectively. Microfilarial density increased rapidly to a peak at 8-12 weeks from patency and then leveled off at about 40-50 mf/20 PL in those infected SC, whereas counts were very low in those infected P. The periodicity indices and peak hours in IP and SC infected animals were 33.4 and 10.04 hrs, and 67.6 and 7.88 hrs, respectively. The appropriate infective dose for infection of jirds for use in the screening of filaricides is 50 L3 either IP or SC.